2007
DOI: 10.1128/mcb.01674-06
|View full text |Cite
|
Sign up to set email alerts
|

Individual Subunits of the Ssn6-Tup11/12 Corepressor Are Selectively Required for Repression of Different Target Genes

Abstract: The Saccharomyces cerevisiae Ssn6 and Tup1 proteins form a corepressor complex that is recruited to target genes by DNA-bound repressor proteins. Repression occurs via several mechanisms, including interaction with hypoacetylated N termini of histones, recruitment of histone deacetylases (HDACs), and interactions with the RNA polymerase II holoenzyme. The distantly related fission yeast, Schizosaccharomyces pombe, has two partially redundant Tup1-like proteins that are dispensable during normal growth. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Tup1p may therefore be responsible for repressor activity, with Cyc8p possibly serving as a bridge between Tup1p and other proteins. S. cerevisiae CYC8, not TUP1, is required for normal growth (30), and the S. pombe ssn6 ϩ gene has also been shown to be essential for growth (31).…”
mentioning
confidence: 99%
“…Tup1p may therefore be responsible for repressor activity, with Cyc8p possibly serving as a bridge between Tup1p and other proteins. S. cerevisiae CYC8, not TUP1, is required for normal growth (30), and the S. pombe ssn6 ϩ gene has also been shown to be essential for growth (31).…”
mentioning
confidence: 99%
“…Previous studies had demonstrated that inv1 ϩ is transcriptionally repressed in high glucose and induced in low glucose (19,35) and that glucose repression depends upon Scr1 and Ssn6/Tup (9,35). Our results show that inv1 ϩ is under the control of a complex set of regulatory elements, spread over approximately 2 kb, a size considerably larger than that normally observed for yeast genes.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have shown that inv1 ϩ transcription is repressed in high glucose and induced in low glucose, yet its regulation is distinct from that of another glucose-regulated gene, fbp1 ϩ (19,35). Additional work has shown that repression of inv1 ϩ in high glucose requires the factors Scr1 (35) and Ssn6/Tup (9). Furthermore, inv1 ϩ is regulated by histone acetylation, as a histone deacetylase, Clr6, is required for the full repression of inv1 ϩ , acetylation of H3K14, H4K12, H4K16, and H4K5 in the intergenic region of inv1 ϩ is elevated in a clr6-1 mutant, and inv1 ϩ mRNA levels are decreased in the absence of the histone acetyltransferase Elp1 (28,38).…”
mentioning
confidence: 99%
“…This is not surprising because it has been previously reported in S. cerevisiae and in other microorganisms that the repression activity of each component of the co-repressor complex may vary depending on the target gene. For example, unlike the TUP1 gene, the CYC8 gene is essential for viability in Schizosaccharomyces pombe [4446]. In addition based on reports that Cyc8 forms a bridge between the DNA-binding regulator and Tup1 [44, 47], Tup1 may not be recruited to the target promoters in the absence of Cyc8.…”
Section: Resultsmentioning
confidence: 99%